2017
DOI: 10.21037/jtd.2017.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene co-expression network analysis in identification of metastasis-related genes of lung squamous cell carcinoma based on the Cancer Genome Atlas database

Abstract: Background: Lung squamous cell carcinoma (lung SCC) is a common type of malignancy. Its pathogenesis mechanism of tumor development is unclear. The aim of this study was to identify key genes for diagnosis biomarkers in lung SCC metastasis. Methods: We searched and downloaded mRNA expression data and clinical data from The Cancer Genome Atlas (TCGA) database to identify differences in mRNA expression of primary tumor tissues from lung SCC with and without metastasis. Gene co-expression network analysis, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…It relies on the assumption that highly correlated genes within a module are involved in common biological processes. For example, Tian et al [13] used WGCNA to identify two gene co-expression modules involved in the process of lung SCC metastasis and suggested that CFTR, SCTR, and FIGF genes could be used as a potential prognostic biomarker. Using WGCNA in the studies of progression and prognosis of breast cancer indicated the relevant correlation of one module of genes with patient survival time.…”
Section: Introductionmentioning
confidence: 99%
“…It relies on the assumption that highly correlated genes within a module are involved in common biological processes. For example, Tian et al [13] used WGCNA to identify two gene co-expression modules involved in the process of lung SCC metastasis and suggested that CFTR, SCTR, and FIGF genes could be used as a potential prognostic biomarker. Using WGCNA in the studies of progression and prognosis of breast cancer indicated the relevant correlation of one module of genes with patient survival time.…”
Section: Introductionmentioning
confidence: 99%
“…ROPN1L variants are significantly associated with high risk of breast cancer in women [31]. Moreover, Tian et al reported that ROPN1L was enriched in lung squamous cell carcinoma [32]. Lowe et al [33] showed that ROPN1L gene was overexpressed in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Their gene signature was statistically associated with overall survival in important clinical subsets (stage I, epidermal growth factor (EGFR) wild-type and EGFR mutant). 2) TIAN et al [111] analysed coexpression networks and protein-protein interactions of data available in public repositories (The Cancer Genome Atlas, KEGG and Gene Ontology).…”
Section: Lung Cancermentioning
confidence: 99%